南極広域観測網による太陽−地球系現象の総合研究 - 門倉, 昭; 山岸, 久雄; 行松, 彰; 宮岡, 宏; 岡田, 雅樹; 小川, 泰信; 田中, 良昌; 片岡, 龍峰; 海老原, 祐輔; 元場, 哲郎; Akira, Kadokura; Hisao, Yamagishi; et al. (2013)
A large observation network with the SuperDARN radars and other ground-based instruments at manned and unmanned stations is currently developed in the Antarctic area from sub-auroral latitudes to polar cap region and from nightside to dayside hours under international collaboration. Such a wide-spread circumpolar observation network is very unique and powerful for studies on the phenomena which occur due to the Sun-Earth interaction, e.g., direct entry of solar wind energy and momentum into the cusp and polar cap regions, explosive energy dissipation during substorm-time, highly energetic particle precipitation into the atmosphere during storm-time. In the coming phase IX of the Japanese Antarctic Research project, coordinated observations with several magnetospheric satellite projects, e.g., MMS (Magnetospheric Multiscale Mission), ERG (Energization and Radiation in Geospace), etc., can be expected 第4回極域科学シンポジウム 特別セッション：[S] 南極研究の将来展望―第Ⅸ期6か年計画策定に向けて 11月14日（木） 国立極地研究所 ２階大会議室 conference object